RIP1 kinase activity is critical for skin inflammation but not for viral propagation. Issue 6 (27th January 2020) - Webster, Joshua D.; Kwon, Youngsu C.; Park, Summer; Zhang, Hua; Corr, Nick; Ljumanovic, Nina; Adedeji, Adeyemi O.; Varfolomeev, Eugene; Goncharov, Tatiana; Preston, Jessica; Santagostino, Sara F.; Patel, Snahel; et al.
Abstract: Receptor interacting protein kinase 1 (RIP1) is a critical effector of inflammatory responses and cell death activation. Cell death pathways regulated by RIP1 include caspase-dependent apoptosis and caspase-independent necroptosis. The kinase activity of RIP1 has been associated with a number of inflammatory, neurodegenerative, and oncogenic diseases. In this study, we use the RIP1 kinase inhibitor GNE684 to demonstrate that RIP1 inhibition can effectively block skin inflammation and immune cell infiltrates in livers of Sharpin mutant ( Cpdm ; chronic proliferative dermatitis) mice in an interventional setting, after disease onset. On the other hand, genetic inactivation of RIP1 (RIP1 KD) or ablation of RIP3 (RIP3 KO) or MLKL (MLKL KO) did not affect testicular pathology of aging male mice. Likewise, infection with vaccinia virus or with mouse gammaherpesvirus MHV68 resulted in similar viral clearance in wild-type, RIP1 KD, and RIP3 KO mice. In summary, this study highlights the benefits of inhibiting RIP1 in skin inflammation, as opposed to its lack of relevance for testicular longevity and the response to certain viral infections.